Community Support Workers’ Experiences of Working During the COVID-19 Pandemic - Ravenswood, Katherine; Hurd, Fiona; Nicholson, Amber; Fromm, Andrea; McCully, Kirsty; Woolley, Melissa; Ewertowska, Tanya (Informa UK Limited, 2023)
This paper investigates the way in which COVID-19 has exacerbated the poor work conditions within community support work in Aotearoa-New Zealand. It examines the invisibility of care work in New Zealand during the COVID-19 pandemic, in terms of Government policy and communication, societal recognition of care work, and the spatially hidden nature of the work. It does so within the of gender norms in the socio-cultural, socio-spatial and socio-legal spheres that render this work and workers invisible. This paper documents the experiences of community support workers and contributes to our theoretical understanding of frontline health workers’ experiences of work during a global public health crisis.
Keywords: 4410 Sociology; 44 Human Society; Generic health relevance; 1503 Business and Management; 1604 Human Geography; 1605 Policy and Administration; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour; 4407 Policy and administration